Hemodynamic Responses to laryngoscopy and intubation: Comparison between Macintosh and McCoy laryngoscope - Joshi, Pankaj; Sigdel, Shailendra; Sharma Bhattarai, Amit; Pradhan, Bishwas (Medical Journal of Shree Birendra Hospital, 2022)
Background: Laryngoscopy causes exaggerated hemodynamics as tachycardia, hypertension, arrhythmias and may have deleterious respiratory, neurological, and cardiovascular effects. A very few studies have compared the effects of various types of laryngoscope blades on hemodynamic response to laryngoscopy and intubation. Methodology: A prospective randomized study was done to compare the hemodynamic response to using McCoy and Macintosh laryngoscope. A hundred patients, belonging to ASA grade I and II, between 15-65 years, requiring general anesthesia with intubation were included. A standard anesthesia technique was used. Both groups(n=50) were matched demographically. Mallampati grading, laryngoscopy and intubation time, laryngeal visualization grades, and hemodynamic variables at baseline were comparable. Result: Following laryngoscopy there was significant rise in heart rate, systolic, diastolic and mean arterial pressure. The maximum change in HR compared to baseline was 20.45±9.29 vs 12.36± 7.28 (p<0.001) in Macintosh and McCoy groups. As compared to baseline maximum change in SBP (mean) was 7.92±10.53 vs 2.80± 6.73 (p= 0.005), the maximum change in DBP (mean) was 9.28±14.74 vs 5.72±7.37 (p= 0.130), the maximum percentage change in MAP (mean) was 8.62±12.07 vs 4.36±7.83 (p=0.039) in Macintosh and McCoy group respectively. Compared to variables just before insertion of the laryngoscope, maximum percentage rise in mean HR was 22.74±10.88 vs 16.40±7.43 (p=0.001), maximum percentage rise in SBP (mean) was 28.31± 13.22 vs 19.41±6.82 (p<0.001), maximum percentage rise in DBP (mean) was 30.00±15.25 vs 24.64±12.21 (p=0.003), maximum percentage rise in MAP (mean) was 28.89±11.55 vs 22.31±11.34 (p=0.05) in Macintosh and McCoy group respectively. Conclusion: The hemodynamic response to laryngoscopy and intubation with McCoy laryngoscope was significantly less than with Macintosh laryngoscope.